Study on AI Technology Empowerment of Smart Farms from the Perspective of Science Communication: A Case Study of Primary and Secondary School Students and Science and Technology Counselor (Contemporary Education and Teaching Research, 2025)
This study is conducted in accordance with China’s strategy for advancing agricultural and rural modernization during the 14th Five-Year Plan period and the requirements of the Central No. 1 Document in 2025. It explores the application of AI technology in smart farms and the value of conducting agricultural-related science communication among adolescents. Given the current situation where primary and secondary school students have certain misunderstandings and a lack of knowledge about modern agriculture, the study investigates the technical logic and social significance of AI technology in addressing educational pain points. It also focuses on the new models of science communication for primary and secondary school students and the transformation of the role of science and technology counselor. Based on the analysis of the actual situations of science popularization lectures and activities, the study proposes research methods to further improve the scientific literacy of primary and secondary school students and the professional capabilities of science and technology counselor.